Studies in Schoenoplectiella (Cyperaceae) in tropical West Africa - Verloove, Filip; Mesterházy, Attila; Browning, Jane (Phytotaxa, 2016)
Schoenoplectiella patentiglumis, a species described from Natal (South Africa) and previously known from Mozambique and Zimbabwe only, is reported for the first time from tropical West Africa (Benin, Burkina Faso and Nigeria) where it has been confused with S. articulata. Schoenoplectiella raynaliana, a rare species only known from the type locality in Togo, is shown to be morphologically conspecific with the widespread African species S. proxima. These findings are the result of examining, measuring, photographing, making notes and illustrations from numerous collections of S. patentiglumis and S. proxima in several different herbaria.